1989
DOI: 10.1210/endo-124-1-77
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Vasopressin and Atrial Natriuretic Peptide in Anesthetized Rabbits*

Abstract: The elimination from plasma of the peptide hormones vasopressin (VP) and atrial natriuretic peptide (ANP) as well as the time course of release and elimination of these hormones after a physiological stimulus were studied in anesthetized rabbits. As an inverse relationship was found to exist between carotid sinus pressure and plasma IR-ANP, a decrease in carotid sinus pressure to 60 mm Hg was used to stimulate ANP as well as VP release. The elimination of VP after iv injection involved a rapid initial phase an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 9 publications
2
8
0
Order By: Relevance
“…of 2Q% of the blood volume increased plasma AVP before, but not after, section of the aortic depressor nerves (Courneya et al 1989). This finding suggested that, under those experimental conditions, a decrease in atrial receptor activity did not contribute to the haemohage-induced increase in AVP.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…of 2Q% of the blood volume increased plasma AVP before, but not after, section of the aortic depressor nerves (Courneya et al 1989). This finding suggested that, under those experimental conditions, a decrease in atrial receptor activity did not contribute to the haemohage-induced increase in AVP.…”
mentioning
confidence: 73%
“…Cardiovascular variables were recorded and a blood sample was taken 10 min after the change in blood volume. We have recently shown that plasma AVP reaches a maximum change within 10 m i w of a physiological stimulus, which either increases or decreases plasma AVB (King et al 1989). The blood volume was the restored to its original value at the same rate as the previous chmge.…”
Section: Protocolmentioning
confidence: 88%
“…The relative roles of these many systems in regulating AVP secretion are incompletely understood, but are clearly not simply additive responses. Following release, AVP is rapidly metabolized by several plasma endopeptidases so that it has a circulating half-life of 1-5 min [386] . Following release, AVP is rapidly metabolized by several plasma endopeptidases so that it has a circulating half-life of 1-5 min [386] .…”
Section: Regulationmentioning
confidence: 99%
“…Blood samples for the measurement of iVP and iANF were taken 10 min after each step change in BV. We have recently shown that changes in iVP in response to stimuli which increase or decrease plasma iVP are usually complete within 10 min (King et al 1989). On a separate group of six New Zealand white rabbits blood volume was measured using chromium-labelled red blood cells and radio-iodinated serum albumin.…”
Section: Protocolmentioning
confidence: 99%